THE IMPACT OF TASK-BASED LANGUAGE TEACHING (TBLT) ON ENHANCING COMMUNICATIVE COMPETENCE IN EFL CLASSROOMS - Berdiqulova Mahbuba Erkinjon qizi; Mehmonova Umidabonu (TADQIQOTLAR, 2026)
ABSTRACT This research paper investigates the profound impact of Task-Based Language Teaching (TBLT) on the development of communicative competence among English as a Foreign Language (EFL) learners. In an era where linguistic accuracy often takes a backseat to functional fluency, TBLT emerges as a bridge between theoretical knowledge and practical application. The study compares the traditional Presentation- Practice-Production (PPP) model with the TBLT framework developed by Jane Willis. By analyzing student engagement, fluency, and cognitive load, the paper argues that TBLT provides a more authentic environment for language acquisition. Results indicate that students taught via TBLT demonstrate higher confidence and a more robust ability to navigate unpredictable communicative situations.